2022
DOI: 10.2147/jir.s363840
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in Immune System and Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a nonspecific inflammatory disease that includes ulcerative colitis (UC) and Crohn’s disease (CD). The pathogenesis of IBD is not fully understood but is most reported associated with immune dysregulation, dysbacteriosis, genetic susceptibility, and environmental risk factors. Vitamin D is an essential nutrient for the human body, and it not only regulates bone metabolism but also the immune system, the intestinal microbiota and barrier. Vitamin D insufficiency is common in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 171 publications
0
30
1
4
Order By: Relevance
“…Existing studies clearly suggest that UC is a group of chronic nonspecific inflammatory diseases of the colon and rectum. According to the current research, the pathogenesis of UC is still unclear, but with the in-depth research of domestic and foreign scholars, it is found that UC may be related to genetics, immunity, susceptibility genes, and environmental factors [ 102 ]. We found that genetic factors play a certain role in the pathogenesis of UC, and psychologically induced factors are also critical in the deterioration of UC.…”
Section: Resultsmentioning
confidence: 99%
“…Existing studies clearly suggest that UC is a group of chronic nonspecific inflammatory diseases of the colon and rectum. According to the current research, the pathogenesis of UC is still unclear, but with the in-depth research of domestic and foreign scholars, it is found that UC may be related to genetics, immunity, susceptibility genes, and environmental factors [ 102 ]. We found that genetic factors play a certain role in the pathogenesis of UC, and psychologically induced factors are also critical in the deterioration of UC.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of inflammatory bowel disease (IBD) is more common in countries located at a higher latitude with reduced exposure to sunlight, similar to T1D and MS [ 227 , 255 ]. IBD presents a defective innate and adaptive immunity, with increased intestinal permeability, and imbalanced gut microbiota, resulting in chronic inflammation of the intestine [ 256 , 257 , 258 ].…”
Section: Vitamin D and Immune-related And Autoimmune Diseasesmentioning
confidence: 99%
“…This suggests that VD deficit may significantly influence IBD development and course, although it is not definitively clarified whether deficiency is the cause of IBDs or malabsorption following IBD development is associated with VD deficiency, and this influences IBD course [ 94 ]. VD deficiency can be detected in about 45–50% of UC patients, whereas it ranges from 35–100% in the case of CrD, and several studies have shown a potential relationship between VD serum levels and disease activity in IBDs [ 95 ]. Ham et al studied this problem in 711 CrD patients and 764 UC patients [ 90 ].…”
Section: Vitamin D and Inflammatory Bowel Diseasementioning
confidence: 99%